Land use dynamics in Iligan City using remotely sensed data and GIS - Trinidad, Metodia M. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2007)
Iligan City is dubbed as the “Industrial Center of the South” as it hosts a number of major industries in the Philippines. One comparative advantage of the city as site for industries over other cities in Mindanao is its proximity to sources of power such as Agus 1 to Agus VII Hydro-electric Power Plants operated by the National Power Corporation (NPC). As an industrial hub, Iligan City becomes one of the fastest growing urban centers in the country. In this paper, satellite data taken in 1998 and in 2005 were compared to assess the change in land use pattern of the city to be able to project possible future land use change. The results indicate an increase in urban land use area of 20%, an increase in agro-industrial area of 9% and a decrease in agricultural land by 6%. Urban growth is located along coastal areas and in some hinterland barangays. The output of this research will serve as tool to planners of Iligan City to guide them in setting policy directions of land development of the city.